Prevalence, incidence, and mortality of stroke in the chinese island populations: a systematic review. - Xiaomei Wu (Public Library of Science (PLoS), 2013)
Background In China, there are 2.5 million new stroke cases each year and 7.5 million stroke survivors. However, stroke incidence in some island populations is obviously lower compared with inland regions, perhaps due to differences in diet and lifestyle. As the lifestyle in China has changed significantly, along with dramatic transformations in social, economic and environmental conditions, such changes have also been seen in island regions. Thus, we analyzed stroke in the Chinese island regions over the past 30 years. Methods We conducted a systematic review to identify reliable and comparable epidemiologic evidence about stroke in the Chinese island regions between 1980 and 2013. Two authors independently assessed the eligibility and the quality of the articles and disagreement was resolved by discussion. Owing to the great heterogeneity among individual study estimates, a random-effects or fixed-effects model was used to incorporate the heterogeneity among records into a pooled estimate for age-standardized rates. Age-standardized rates were calculated by the direct method with the 2000 world population if included records provided the necessary information. Results During the past three decades, the overall pooled age-standardized prevalence of stroke is 6.17 per 1000 (95% CI 4.56-7.78), an increase from 5.54 per 1000 (95% CI 3.88-7.20) prior to 2000 to 8.34 per 1000 (95% CI 5.98-10.69) after 2000. However, this difference was not found to be statistically significant. The overall pooled age-standardized incidence of stroke is 120.42 per 100,000 person years (95% CI 26.17-214.67). Between 1982 and 2008, the incidence of stroke increased and mortality declined over time. Conclusions Effective intervention and specific policy recommendations on stroke prevention should be required, and formulated in a timely fashion to effectively curb the increased trend of stroke in Chinese island regions.